The role of university entrepreneurship support and student diversity in student entrepreneurial intention: a social identity theory perspective. - Tamara Ratkovic; Ivan Paunovic; Helena Šlogar (PLoS ONE)
One of the most significant shortcomings of the extant literature is the dearth of conceptualizations and empirical testing pertaining to entrepreneurial diversity and the underlying social identities. Accordingly, this research aims to empirically investigate the influence of entrepreneurial support at the university level on students' entrepreneurial intention from a diversity and social identity perspective. The research utilizes fsQCA (fuzzy set Qualitative Content Analysis) and a set of observable and underlying diversity factors (gender, age, previous academic performance, and parental educational attainment) to elucidate the causal structures that influence the formation of entrepreneurial intention among university students. The findings illustrate the multifaceted nature of the entrepreneurial intention formation, with first-generation status being a necessary condition for low entrepreneurial intention. The findings underscore the importance of university entrepreneurial support in the formation of entrepreneurial intention especially for younger students and first-generation students. The study contributes to the literature on entrepreneurial diversity and social identities in entrepreneurship by identifying the underlying factors that contribute to high and low entrepreneurial intention among university students.